Sustainable public procurement: its origin and development (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2023)
The weight of public sector contracting in Europe, that is, its purchasing power represents around 15% of European GDP. It is, therefore, a powerful instrument that can and should also help to improve the environment and more sustainable development.This work analyzes the conceptual framework of contracting with environmental criteria, the importance of a public policy that internalizes the objectives of sustainable development, with a very high capacity to influence the market and an exemplary component in the action of administrations and its relationship with common goods and with citizens. The article refers to the beginnings of green purchasing, with a specific section on the main actors who acted as driving forces of change. Next, the legislative development in the European community framework is explained, as well as its regulatory translation to Spain and the Autonomous Communities.Due to their practical value, two pioneering cases in Spain are presented - Barcelona City Council and the Basque agency IHOBE - summarizing the evolutionary development of the inclusion of environmental clauses in our contracting, both in the field of the regulatory framework and management. A section is included on the evaluation of a sustainable purchase, to end by suggesting some of the challenges that we still have in this area. The object of the work is a public policy that, in a period of 25 years, has developed in an unthinkable way and with globally very positive results.
Keywords: public procurement; sustainable procurement; green purchasing; environmental clauses; public policies